THE TERM OF “RELEVANT MARKET”, AS ELEMENT OF DOMINANT POSITION PROVIDED BY ART. 102 OF THE TREATY ON THE FUNCTIONING OF THE EUROPEAN UNION - Cornelia Beatrice Gabriela ENE-DINU (Challenges of the Knowledge Society)
The term of relevant market was used for the first time in the Sherman Act of 1890, condemning monopolies or monopoly attempts. The term of relevant market is analyzed as being the place where demand and supply of products or services, interchangeable with each other, are confronting; however, the term of "relevant market” is much more complex than that, being characterized by fundamental dimensions in connection with the term of product (service) market and geographic market, both in close connection.